Information security incident management using iso 27035 standard - Poetiray, Ignatius Frank Zinatra; Salman, Muhammad (Universitas Wiralodra, 2023)
The data and information management process at BMKG entails certain risks related to information security incidents. There needs to be more emphasis on addressing these incidents regarding policies, procedures, technology, and human resources. This research project aims to develop an incident management system by ISO 27035 standards. Qualitative research methods have been employed for BMKG Communication Network Center case studies. The approach involves aligning information security incident management with BMKG's business processes. The outcome of this research includes creating policies, documents, and standardized procedures designed to enhance BMKG's capabilities in effectively managing and mitigating incident threats.